Adoption and Utilization of Information Technology in Agriculture: Evidence from Rupendehi, Nepal (Quest Journal of Management and Social Sciences, 2025)
Background: The use of information technology (IT) in agriculture is expanding globally however, its adoption among farmers in Nepal remains uneven. Several factors, including education, location, cost of equipment, and political support, may affect how farmers integrate IT tools into their farming practices. This situation is particularly relevant in mixed farming areas such as the Rupandehi district.Purpose: The main objective of this study is to identify the major factors that influence farmers' adoption and use of IT in Rupandehi, Nepal. It also seeks to examine how variables such as educational background, financial condition, policy support, and geographic location affect IT adoption and to relate these outcomes to previous studies.Design/methodology/approach: A quantitative research design was applied using a structured questionnaire distributed to 402 farmers. The collected data were analyzed using structural equation modeling (SEM) to test relationships between education, political support, equipment cost, and geographic location as predictors of IT adoption. The reliability and validity of the questionnaire were examined using Cronbach's alpha and factor analysis.Findings: The findings from SEM revealed that political support had the strongest positive impact on IT adoption (β = 0.497, p < 0.001), followed by equipment cost, which had a moderate positive effect (β = 0.175, p < 0.001). Unexpectedly, higher levels of formal education were found to have a negative relationship with IT adoption (β = −0.258, p < 0.001), whereas geographic location had no significant effect. The model explained 73.8% of the total variance in IT adoption, confirming its reliability and validity.Conclusion: The study concludes that consistent political and extension support, affordable equipment, and practical digital training are essential for promoting agricultural digitalization. The negative influence of higher education suggests a need for more targeted, context-based digital skill programs. Future qualitative research across multiple districts is encouraged to explore these findings further.Keywords: Agriculture, Adoption, Information Technology, Rupandehi, Nepal